The Role of Rainfed Farming on Farm Household Income in Waru Village Bantarkawung Brebes - Ryan Saiful Ghani; Istiqomah Istiqomah; Ratna Setyawati Gunawan (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Agriculture is the major contributor to the Brebes Regency's Gross Regional Domestic Product and employment, and rice constitutes the principal crop. Bantarkawung District is the leading producer of rice in the Brebes Regency. However, most of the paddy fields in Bantarkawung are rain-fed, so rice growing is hindered during the dry season due to a water shortage. This study's objective is to assess the farm profits obtained by households and the contribution of rice farming to household income. The population comprises 445 rice-farming families in Waru Village, from which 82 rice farmers were randomly selected. Interviews with respondents were conducted in March 2022. The variables include revenue, costs, profit, and household income. The analytical instruments consist of profit analysis and income contribution. Profit analysis was calculated using the R/C ratio, and the income contribution was calculated by comparing the profit of rainfed rice farming with farm household income. The results indicate that rainfed rice cultivation in Waru Village is profitable. The R/C is more than one, in the range of 1.22 to 2.10. Nonetheless, the contribution of rainfed rice farming to household income is small, ranging from 0.7% to 22.85%. The findings suggest that rainfed rice farmers in Waru Village should be able to sustain their farms because this type of cultivation is profitable despite its reliance on rainwater for irrigation. In addition, it is envisaged that the government, through the appropriate agencies, will enhance the road infrastructure to enable the transfer of agricultural inputs and outputs, offer the necessary socialization, and help boost production.